Career internationalization strategies by women in brazilian independent external auditing - Cunha, Victoria Barboza de Castro (Contextus - Revista Contemporânea de Economia e Gestão, 2024)
Background: Corporate expatriation has become a recurrent practice in global service firms, as these organizations increasingly demand professionals aligned with their internationalization goals. However, there is still a scarcity in the national literature regarding women's expatriation in external audit firms, a field of activity admittedly marked by the glass ceiling phenomenon. Hence, we depart from the premise that Brazilian independent auditors must undertake distinctive strategies to overcome the unequal access to expatriation opportunities provided by the firm, which determine their career progression. Purpose: The aim is to examine the career internationalization strategies of five Brazilian senior auditors. Method: This exploratory qualitative study collected data through remote narrative interviews, whose transcripts were analyzed according to Creswell and Poth (2018). Results: Both active and passive strategies are undertaken. Active strategies included socialization and the strengthening of technical skills. The passive ones included career withdrawal and self-initiated expatriation. Conclusions: The essentially masculinized nature of the independent auditor profession plays a negative role in women's identity capital, despite allowing for accelerated career capital growth as a compensatory element.